Pengunaan Peta Konsep Untuk Belajar Bermakna Dan Peningkatan Pemahaman Siswa Dalam Pembelajaran Biologi - Jailani Jailani (Jurnal Biology Education, 2017)
One of the effort to increase the instructional effectiveness is by developing meaningful learning strategy throught using the concept mapping. The instructional objectives at school is not only to increase the academical achievement but also the ability and skill of the students in order to be able to understand the process of inproving knowledge, attitude to the subject which is studied and attitude to the environment, too. The instructional strategy whith the concept mapping is one of thealternatives that can provide the result of all aspects that is hoped to reach the instructional objectives. The concept mapping learning strategy signifies the students reorganize the new knowledge by inserting the concept into the net hierarchily and discribe their connection in a diagram and the combine it into a greater knowledge structure. The organizing of conceptual undestanding well will aid the meaningfulness of students learning, so, the students are easier to understand the material of the lesson being studied.